Addressing the problem of inaccuracy of measured 24‐hour urine collections due to incomplete collection. Issue 11 (21st October 2019) - Mann, Samuel J.; Gerber, Linda M.
Abstract: The 24‐hour urine collection is widely considered the gold standard for assessing 24‐hour excretion of various analytes. Yet, studies show that >30% of collections are incomplete and hence understate the true 24‐hour excretion. We previously validated an equation for estimating an individual's 24‐hour creatinine excretion, based on weight, sex, race, and age. The present study examines whether routinely correcting measured 24‐hour excretion of an analyte using the ratio of estimated to measured 24‐hour urine creatinine mitigates the misleadingly low values that result from undercollection. Ninety‐nine participants, recruited from an outpatient hypertension clinic, submitted a 24‐hour urine collection for measurement of creatinine and sodium excretion. The urine collections were dichotomized into complete (n = 63) and incomplete (n = 36) collections based on previously described criteria for expected 24‐hour creatinine excretion. To adjust for possible incompleteness of collections, the measured 24‐hour values were then corrected by multiplying them by the ratio of estimated to measured 24‐hour urine creatinine. The mean 24‐hour creatinine excretion was 1682 mg/d among complete collectors. Among incomplete collectors, the mean was 1211 mg/d before and 1695 mg/d after, adjustment. Similarly, mean 24‐hour sodium excretion was 156 mEq/d among complete collectors, whereas among incomplete collectors it was 121 mEq/d before and 171 mEq/d after, adjustment. Undercollection of 24‐hour urines is a common problem and results in misleadingly low values for excretion of analytes being measured. Routine adjustment of 24‐hour urine values using estimated values for 24‐hour creatinine excretion can greatly mitigate artifactually low 24‐hour excretion results.